DYNAMIC MODEL OF SUSPENSION SYSTEM REFLECTING COMPLEX MECHANICAL CHARACTERISTICS OF BUSH - FENG JinZhi; GAO RuoQi; ZHENG SongLin; LIU ShuFan; ZHANG QiTao; GU Han (Jixie qiangdu)
Dynamic simulation is an indispensable means for the development of advanced suspension system. The accuracy of the model affects the efficiency of product development. The bushing components in suspension system have a great influence on the vehicle performance, so it is necessary to describe its complex nonlinear mechanical characteristics accurately when modeling the suspension system dynamics. However, the suspension bush model built in Adams can only roughly reflect its basic mechanical characteristics. In this paper, a high order fractional derivative three element parallel bushing mathematical model is applied. This model can better describe the higher-order and non-linear of the mechanical characteristics of the bushing viscoelastic element. Based on Visual Studio Intel Visual Fortran platform, combined with FORTRAN language and Adams built-in function rules, completed the compilation and compilation of bushing mathematical model, and built a suspension system dynamic simulation platform. Finally, sinusoidal sweep frequency, cement crack spectrum and S-curve excitation test are carried out on the dynamic K ＆ C test-bed to verify the proposed modeling method.